Constitutional openness in 1991, Ethnic and Cultural Diversity, and Political System: a Philosophical-Political Approach - Cuchumbé Holguín, Nelson Jair; Universidad del Valle, Cali, Colombia (Editorial Pontificia Universidad Javeriana, 2012)
The multicultural approach seems to be the most praiseworthy instrument through which the acknowledgement of cultural diversity could renew the deontic structure legitimised by the socio-political order in Colombia. Facing a State model based on the denial and exclusion of diversity, the multicultural State allows for pluralism to be articulated into it. In this way, the formation of political unity becomes a matter determined by dialogue, mutual acknowledgement and cultural enhancement. Nevertheless, the multicultural interpretation lacks plausibility if the formation of the State is understood in a pragmatic and universalistic way. From this perspective, the inclusion of the Other is likely only if social actors promote interactions regulated by a political culture based on constitutional principles, active participation, public deliberation and the organisational ability of communities. A shared political culture of this nature seems unavoidable if the purpose is to form a citizenship more suited to living in a democracy.